2020
DOI: 10.3389/fnmol.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor-Dependent microRNA Expression Profile in the Brain Following Status Epilepticus in Mice

Abstract: The ionotropic ATP-gated P2X7 receptor is an important contributor to inflammatory signaling cascades via the release of Interleukin-1β, as well as having roles in cell death, neuronal plasticity and the release of neurotransmitters. Accordingly, there is interest in targeting the P2X7 receptor for the treatment of epilepsy. However, the signaling pathways downstream of P2X7 receptor activation remain incompletely understood. Notably, recent studies showed that P2X7 receptor expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 97 publications
4
6
0
Order By: Relevance
“…Both genotypes experienced similar seizures during status epilepticus ( Figure 4 B), in line with previous studies using the same transgenic P2X7 −/− mouse model [ 34 ]. This suggests differences in cytokine profiles are not due to differences in seizure severity between genotypes.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Both genotypes experienced similar seizures during status epilepticus ( Figure 4 B), in line with previous studies using the same transgenic P2X7 −/− mouse model [ 34 ]. This suggests differences in cytokine profiles are not due to differences in seizure severity between genotypes.…”
Section: Resultssupporting
confidence: 90%
“…Differences in seizure severity and epilepsy development between genotypes may also compensate changes in cytokine expression or increase differences between genotypes. However, as reported previously [34], both wt and P2X7 −/− mice experienced similar seizures during status epilepticus. Whether this is the case for epilepsy development remains to be established.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This ATP serves as a damage-associated molecular pattern (DAMP) which is detected by microglial cells via their purinergic receptors. From amongst both ionotropic (P2X) and metabotropic (P2Y) ATP-gated purinergic receptors ( Huang et al, 2019 ), the P2X7R has attracted most attention due to its unique characteristics such as its low affinity to ATP ( Surprenant et al, 1996 ) and the suggested involvement in a broad range of neurodegenerative diseases such as AD ( Martin et al, 2019 ; Francistiová et al, 2020 ), epilepsy ( Engel et al, 2012 ; Conte et al, 2020 ; Morgan et al, 2020 ), schizophrenia ( Calovi et al, 2020 ), Huntington’s disease ( Ollà et al, 2020 ) and many others. Moreover, another property of the P2X7R is its ability to induce macropore formation upon exposure to high concentrations of ATP ( Di Virgilio et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%